The application of Seismic Coefficients in simple earthquake-resistant houses - Sutrisno Sutrisno; Agus Budiono (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
After an earthquake, reconstruction and rehabilitation are often carried out. One of them is by building a simple house. A simple house is the one built without involving construction experts, and hence it rarely follows earthquake-resistant building regulations. This study aims to determine and apply seismic coefficient in the planning of earthquake-resistant, simple houses. The seismic coefficient calculation is applied by comparing the maximum ground acceleration with gravity in cities in three provinces, namely Banten, DKI Jakarta, and West Java. From the calculation results in 21 cities in 3 provinces, the obtained seismic coefficient ranges from 0.175 to 0.411. The smallest seismic coefficient occurs in Indramayu, while the largest seismic coefficient occurs in Sukabumi. Based on the seismic coefficient, the level of earthquake risk for simple house buildings can be known. The lowest risk level occurs in Indramayu with the value of 17.5% and the highest risk level is in Sukabumi with the value of 41.1% of the standard price of a simple house building in each city. The risk level difference from one city to another can be used to strengthen and save the cost of building simple, earthquake-resistant houses.©2021 JNSMR UIN Walisongo. All rights reserved.